Why do people present late with advanced glaucoma? A qualitative interview study. Issue 12 (24th September 2013) - Prior, Maria; Francis, Jill J; Azuara-Blanco, Augusto; Anand, Nitin; Burr, Jennifer M; ,
Abstract : Objective: To explore the presentation behaviours and pathways to detection of adults who first presented to UK hospital eye services with severe glaucoma. Design: Semistructured interviews, based on models of diagnostic delay, to obtain a descriptive self-reported account of when and how participants' glaucoma was detected. Results: 11 patients participated (five in Aberdeen, six in Huddersfield). Four participants reported that the optometry appointment at which their glaucoma was detected was their first ever eye test or their first for over 10 years. Seven participants reported attending regular routine optometrist appointments. Their self-reported experiences and pathways to detection describe a variety of missed detection opportunities and delayed referral and treatment. Conclusions: The qualitative data suggest that late detection of glaucoma can result from delays at the patient level but, although based on a small sample, delays also occurred at the healthcare provider (system) level both in terms of accuracy of case detection and effective referral. We suggest that current attempts to address the significant burden of over-referral of glaucoma suspects to hospital eye services (a large proportion of which are false positives) must also focus on the issue of false negatives and on reducing missed detection and service delays.